2006
DOI: 10.2174/157018006776286943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of a New Drug on Brain Leukocyte Infiltration in an Experimental Model of Autoimmune Encephalomyelitis

Abstract: Experimental Autoimmune Encephalomyelitis (EAE) was induced for the evaluation of a new drug candidate (GEM-SP) for multiple sclerosis. Using immunocytochemical techniques with a pan-leukocyte marker, "anti-CD 45", differential leukocyte infiltration was compared in different experimental groups: 1) EAE-immunized rats treated with GEM-SP; 2) EAE-immunized rats treated with NaCl; 3) EAE-immunized rats treated with free constituents (not linked to inert carrier protein) and the inert carrier protein of GEM-SP. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…, vitamins) coupled to PLL represent a low weight proportion of the whole PLL-compound molecular weight; iii) PLL compounds are not transporters of small molecules (they are not neither vectors nor liposomes); it should be noted that free constituents (small molecules not linked to PLL) have no effect since they are quickly incorporated into the metabolism and only PLL-compounds have a beneficial effect as previously reported; 12,52 in sum, PLL-compounds have an effect only when small molecules are linked to the PLL and neither free small molecules nor PLL alone have effect; 12,52 and iv) free small molecules are quickly degraded or incorporated to metabolism, but when they are linked to PLL the half-life is longer as well as their effects; for this reason the dose of PLL compounds is much lower than currently standard drugs.…”
Section: Discussionmentioning
confidence: 77%
“…, vitamins) coupled to PLL represent a low weight proportion of the whole PLL-compound molecular weight; iii) PLL compounds are not transporters of small molecules (they are not neither vectors nor liposomes); it should be noted that free constituents (small molecules not linked to PLL) have no effect since they are quickly incorporated into the metabolism and only PLL-compounds have a beneficial effect as previously reported; 12,52 in sum, PLL-compounds have an effect only when small molecules are linked to the PLL and neither free small molecules nor PLL alone have effect; 12,52 and iv) free small molecules are quickly degraded or incorporated to metabolism, but when they are linked to PLL the half-life is longer as well as their effects; for this reason the dose of PLL compounds is much lower than currently standard drugs.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, many studies have shown the therapeutic effects of vitamins. Thus, (1) vitamin K has been used as a possible therapy in an animal model of multiple sclerosis [91], (2) populations with a regular intake of vitamin E have a lower risk of amyotrophic lateral sclerosis than nonuser populations [92], (3) α-tocopherol succinate is a component of GEMSP owing to its interactions with ROS and NO [93], and (4) a vitamin A metabolite (all-trans retinoic acid) has been shown to exert a therapeutic effect in an experimental autoimmune nephritis model [94]. The possible therapeutic implications of vitamins open new perspectives as regards the involvement of such substances in neurodegenerative diseases.…”
Section: Possible Functional Roles Of Vitaminsmentioning
confidence: 99%
“…In preclinical studies (acute model of EAE) (10), it has been reported that GEMSP (0.75 mg/day) inhibited brain leukocyte infiltration (10). Later, in a chronic model of EAE, it was demonstrated that GEMSP (7.5 mg/day) abolished EAE episodes, the clinical score and brain leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of GEMSP have been demonstrated in acute and chronic experimental autoimmune encephalomyelitis (EAE) models (10,11).…”
Section: Introductionmentioning
confidence: 99%